Mitigation of foreign Direct investment risk and hedging - Jack E. Wahl; Udo Broll (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
Instruments of risk mitigation play an important role in managing country risk within the foreign direct investment (FDI) decision. Our study assesses country risk by state-dependent preferences and introduces futures contracts as a tool of risk mitigation. We show that country risk assessments related to foreign direct investment do not matter if the multinational firm enters currency futures markets. Besides currency risk, multinationals cross-hedge country risk via the derivatives market. This may explain the empirical result, why host country risk is not a significant determinant of FDI (Bevan/Estrin 2004) together with the fact that almost all (92 %) of the world's top 500 companies enter derivatives markets for hedging purposes (ISDA 2008).
Keywords: F21; F23; G32; 330; state-dependency; country risk; foreign direct investment; hedging; Multinationales Unternehmen; Direktinvestition; Länderrisiko; Hedging; Währungsmanagement; Theorie